Investigação de genes de resistência a antimicrobianos e da capacidade de formação de biofilme em isolados de Salmonella Enteritidis - Puffal, Júlia (2013)
Salmonella Enteritidis is the most prevalent serotype isolated in Brazil, mainly associated with poultry products, which have been primarily involved in foodborne disease outbreaks. The high prevalence of reduced susceptibility to antimicrobial agents in various Salmonella serotypes isolated from samples related to livestock animal, animal foods and human has been reported worldwide. Therefore, has increased the interest in investigating the genetic mechanisms involved in resistance to antimicrobial agents, especially genetic elements capable of carrying resistance genes cassettes, which could be the origin of multi-resistant strains. Besides the genetically determined antimicrobial resistance, bacteria can also exhibit resistance by the ability to form biofilm, which protects bacteria from environmental stresses, favoring the colonization and persistence of these microorganisms in the environment. Thus, the aim of this study was to determine the antimicrobial susceptibility of S. Enteritidis strains and investigate the genes involved in the main resistance determined, as well as evaluate the ability of these strains in to produce biofilm. Forty-seven S. Enteritidis strains isolated from human, poultry, swine, and food were analyzed. Sixteen isolates (34%) were phenotypically resistant to at least one antibiotic tested. Of these, four isolates harbored class 1 integron. All strains resistant to sulfonamide had concomitantly genes sul1 and sul2. The genes strA, strB, aadA and aadB were identified in the majority of the aminoglycosides resistant isolates, whereas 92.9% showed strA, 71.4% strB, 7.1% aadA and 50% aadB. The tetB gene was detected in two of the three strains resistant to tetracycline, and tetC in one. In the three strains resistant to ampicillin the blaTEM gene was detected. Overall, among the 47 S. Enteritidis tested, 89.4% strains were able to form biofilm on polystyrene plates. Among these, 42.4% were considered weak biofilm producers, 14.9% moderate producers and 34% strong producers. It has been demonstrated that the majority of the S. Enteritidis strains that showed resistance to at least one antimicrobial agent were able to form biofilm, which increases concerns about food contamination, especially by the possibility of persistence of bacteria resistant to antibiotics on the environment and the subsequently dissemination of these strains to human.